Reorientation of Special Education in Improving Self Help Of Children with Special Need - Yasmin Hussain; Mazmi Maarof (Department of Special Education, 2017)
Effective special educational delivery for children with special needs is very crucial and pertinent for the development of the children’s growth, knowledge and living skills. Special Education is indeed a volatile and changeable field and very dynamic as it constantly needs to change and reorient to cater the needs of special children. In anticipation of the global changes in the 21st century, educating children with special needs is no longer confined within the four walls but is an education that needs and must prepare these children towards independence and able to contribute and support to the community as individuals with self-respect. This paper explicates the importance of employability for children with special needs as means of self-help by changing the landscape of education aspects from academic based education setting towards vocational and self-reliance settings through programs that enhanced and expounded on the children’s knowledge and living skills. This is a necessary orientation of Special Education field that is important to help children to become independent adults with strong foundation of Special Education received in their schooling lives